Klasifikasi Pendapatan Driver Shopee Food Menggunakan Metode K-Means - Ariq Azhar Zhafari; Supatman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
PT Shopee Internasional Indonesia is a company that has e-commerce features and also has a food and food delivery service known as Shopee Food which started operating in April 2020. At the beginning of 2021, Shopee Food started fulfilling food and drink orders, thereby attracting many driver partners to deliver it to consumers. This is because the payment system is easy to use. The income received by drivers through ShopeePay is accumulated and properly recorded in the Shopee Food driver account. Therefore, it is necessary to classify a driver's income every week to find out the highest and lowest income. The aim of the research carried out is grouping to minimize the objective function set in the clustering process, which basically tries to minimize variation within one cluster and maximize variation between clusters, and to classify several incomes based on the K-Means method. The research method used is the K-Means clustering method which is used to group data into several groups (clusters) based on similar features. Data collection was carried out for 5 months (May-October) 2023. Then the data obtained was identified in which week the income data was the highest and lowest. So the clustering is carried out which is displayed in the diagram by marking 4 features to make it easier to read the results, namely red (low), blue (medium), black (highest), and blue box (average). The results obtained based on diagrams (visual data) produce the highest data in the 1st month with income of IDR 39,000.00, while the lowest data is in the 4th month with IDR 6,400.00 and with a small data ratio. The conclusion obtained from the research results is that you get the highest income, namely in month 1 with an income of IDR 39,000.00.